Hubungan Pengetahuan dengan Perilaku dalam Penggunaan APAR pada Karyawan di PT. Adhi Persada Gedung Bekasi 2018 - Ahmad Farid Umar; Wilda Margatama (STIKes Persada Husada Indonesia, 2019)
APAR (Fire Extinguishers) is one of the active fire protection system which is easy to carry or lifted by employees when there are small fires and nearest to the employee. So that knowledge against the behavior of the use of APAR (Fire Extinguishers) much needed. The aim of research to find our relationship of knowledge with behavior in the use of APAR, the type of research, correlation studies, cross sectional approach, the study subjects were employee of PT Adhi Persada Gedung Bekasi. The research process has been conducted in May-June 2018 in PT Adhi Persada Gedung-Proyek Grand Dhika City Bekasi. Total population of 161 respondents and the sample of 62 respondents. The method used in sampling is accidental sampling. Results of the study showed most respondents who are at a high level of knowledge (n = 32) and behavioural use of APAR respondents most often behave less (n = 33). There was a significant relationship beetween knowledge with behavior in the use of APAR (P-value = 0,000), means that the knowledge of the respondents affects the behavior of the use of APAR, most respondents with high knowledge tend levels have good behavior in the use of APAR. To increase employee knowledge about the use of APAR, the HSE team continues to hold APAR training on an ongoing basis, it is necessary to conduct ongoing socialization after the training in each safety morning talk to remind them about how to use APAR.